Novel radiation sources using relativistic electrons - Rullhusen, P (World Scientific, 1998)
Series on synchrotron radiation techniques and applications ; vol. 4; Includes bibliographical references and index; 10 chapters: Introduction; Radiation by Relativistic Electrons; Synchrotron Radiation, Undulators, Free - Electron lasers; compton scattering of laser light; cohernt Bremsstrahlung;...